2022
DOI: 10.3389/fendo.2022.951344
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal androgen treatment impairs the suprachiasmatic nucleus arginine-vasopressin to kisspeptin neuron circuit in female mice

Abstract: Polycystic ovary syndrome (PCOS) is associated with elevated androgen and luteinizing hormone (LH) secretion and with oligo/anovulation. Evidence indicates that elevated androgens impair sex steroid hormone feedback regulation of pulsatile LH secretion. Hyperandrogenemia in PCOS may also disrupt the preovulatory LH surge. The mechanisms through which this might occur, however, are not fully understood. Kisspeptin (KISS1) neurons of the rostral periventricular area of the third ventricle (RP3V) convey hormonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 106 publications
2
1
0
Order By: Relevance
“…In view of the recent evidences highlighting the role of RP3V Kisspeptin and VMHvl nNOS neurons in lordosis behavior in healthy female mice ( 65 ) as well as in the PAMH mouse model of PCOS ( 76 ), we would have expected some changes in cFOS in the RP3V and VMHvl region. As noted earlier RP3V Kisspeptin neurons remain unchanged in the PNA mice (data showed here and recently published ( 79 ). Similarly, a previous study from our group showed no changes in arcuate nucleus nNOS neurons in the PNA mice contrary to the PAMH mouse model ( 76 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In view of the recent evidences highlighting the role of RP3V Kisspeptin and VMHvl nNOS neurons in lordosis behavior in healthy female mice ( 65 ) as well as in the PAMH mouse model of PCOS ( 76 ), we would have expected some changes in cFOS in the RP3V and VMHvl region. As noted earlier RP3V Kisspeptin neurons remain unchanged in the PNA mice (data showed here and recently published ( 79 ). Similarly, a previous study from our group showed no changes in arcuate nucleus nNOS neurons in the PNA mice contrary to the PAMH mouse model ( 76 ).…”
Section: Discussionsupporting
confidence: 90%
“…The levels of three domains of male-like sexual behaviors (latency to mount, mounting behavior and pelvic thrusting) were indistinguishable between PNAF mice and control females. These behavioral findings were supported by anatomical data demonstrating a feminized AVPV kisspeptin population as already described ( 79 ). AVPV kisspeptin neurons are a clearly sexually differentiated population in the brain, with the number of neurons decreased by the male-typical prenatal testosterone rise ( 67 ).…”
Section: Discussionsupporting
confidence: 86%
“…Brain slices were prepared as previously described ( 52 , 53 ). Briefly, mice were decapitated following isoflurane anesthesia, and their brains quickly removed.…”
Section: Methodsmentioning
confidence: 99%